Acupoint injection in improving pain and joint function of knee osteoarthritis patients: A protocol for systematic review and meta-analysis. Issue 12 (26th March 2021) - Wang, Houyi; Sun, Jinxu; Yu, Xiuying; He, Yong
Abstract: Background: Knee osteoarthritis is a common chronic progressive disease, which seriously affects the quality of life of the middle-aged and elderly, and even leads to disability. More and more evidence shows that acupoint injection is beneficial to the clinical treatment of knee osteoarthritis, but there are differences in the efficacy of different acupoints and injection drugs, and there is no systematic review to assess this therapy at present. The purpose of this study is to systematically evaluate the efficacy and safety of acupoint injection in improving pain and joint function in patients with knee osteoathrosis. Methods: According to the retrieval strategy, we will search from CNKI, Wanfang, VIP, Chinese Biomedical Science, PubMed, Embase, Web of Science and the Cochrane Library for randomized controlled trials of acupoint injection in the treatment of knee osteoarthritis from the establishment of the database to February 2021. The study will be screened according to the inclusion and exclusion criteria, and the Cochrane risk bias assessment tool will be used to evaluate the quality of the study. Revman 5.4 software is used for meta-analysis. Results: This study will evaluate the efficacy of acupoint injection in the treatment of knee osteoarthritis by evaluating the total effective rate, the degree of pain relief, joint function score, adverse reactions, and so on. Conclusion: This study will provide reliable evidence-based basis for the clinical application of acupoint injection in the treatment of knee osteoarthritis. Ethics and dissemination: Private information from individuals will not be published. This systematic review also does not involve endangering participant rights. Ethical approval will not be required. The results may be published in a peer-reviewed journal or disseminated at relevant conferences. OSF Registration number—doi: 10.17605/OSF.IO/M5FTK.